Effective fractionation of microalgae biomass as an initial step for its utilization as a bioenergy feedstock. (December 2022) - Martins, Pedro L.; Reis, Alberto; Duarte, Luís C.; Carvalheiro, Florbela
Highlights: S. obliquus was effectively fractionated by mild (un)catalyzed hydrothermal processes. Soluble sugars were mainly present as soluble oligosaccharides. Protein was mainly retained in the solid fraction. Dilute acid hydrolysis allowed higher oligosaccharides yield at mild conditions. Co-production of added-value oligosaccharides in marine biorefineries. Abstract: Scenedesmus obliquus, a biotechnologically relevant microalgae, was grown in 70 L vertical photobioreactors using non-supplemented secondary brewery wastewater as a culture medium. Upon collection, by mechanical means, the cells were subjected to hydrothermal (autohydrolysis) and dilute acid hydrolysis (0.5 % sulfuric acid) pre-treatments carried out using pressure micro-reactors under isothermal conditions up to 300 min. Both processes enabled a high recovery of soluble sugars (∼50 %) that were, in a great majority, present in the added-value oligomeric form (92 % and 90.5 % for autohydrolysis and dilute acid hydrolysis, respectively). Protein solubilization also presented relevant yields (35 % removal), with dilute acid hydrolysis allowing both higher oligosaccharides and protein productivities at a milder temperature. As compared to the current whole microalgae biomass-based upgrade strategies, the use of these mild processes is extremely promising, as they will enable the future co-production of added-value oligosaccharides, and protein, which can be relevant co-products of a biofuels-based biorefinery.